Anticorrosive epoxy coatings containing ultrafine bamboo char and zinc particles. Issue 4 (August 2021) - Wang, Xiang; Zhang, Xuefeng; Caldona, Eugene B.; Leng, Weiqi; Street, Jason; Wang, Guoping; Zhang, Zhao
Abstract: Zinc rich epoxy coatings (ZRECs) are widely used to protect steel from aggressive corrosive offshore conditions. However, zinc is known to be harmful to human health and aquatic life. The development of ZREC with a reduced zinc content and good corrosion resistance is desirable but remains a challenge. Herein, a greener ZREC with low-zinc-content (22 wt%) and superior corrosion protection for steel was developed via a common ZREC synthetic process by simply substituting zinc particles with biobased ultrafine bamboo char (UFBC) particles. Relatively small-sized (one order smaller than zinc particles), UFBC particles are abundant in surface functional groups and facilitate the dispersion of zinc particles for effective spray coating and the formation of intact coating films with fewer defects. Moreover, the incorporation of UFBC increases the surface hydrophobicity of the coatings. Results obtained from impedance measurements and salt spray tests show that the UFBC-based ZREC (UFBC/ZREC) can provide more than 35 d of effective protection for mild steel against aggressive 5 wt% NaCl, both in solution and atmospheric environments. Analyses acquired from scanning electron microscopy and X-ray photoelectron spectroscopy indicate that the enhanced corrosion protection of UFBC/ZREC is attributed to the increased coating barrier property and inhibitory actions of zinc particles. Furthermore, the life cycle assessment and economic analyses demonstrate that our UFBC/ZREC is superior to the neat ZREC in terms of eco-friendliness and economics. Graphical Abstract: ga1 Highlights: "Greener" and novel anticorrosive zinc-rich epoxy coatings (ZRECs) containing ultrafine bamboo char (UFBC) were synthesized. UFBC-based ZRECs (UFBC/ZERCs) was prepared via a typical ZERC synthetic process. UFBC/ZERCs exhibited superior protection performance for steel than the neat ZREC. The anticorrosive protection mechanisms of UFBC/ZREC were proposed.